A key to species of Nomada ruficornis species-group (Hymenoptera: Apidae) of South Korea, with descriptions of three new species - Lim, Kayun; Lee, Seunghwan (Zootaxa, 2023)
In this study, three new species (Nomada adustaspinae, sp. n., Nomada atra, sp. n., Nomada biaulacis, sp. n.) and two species new to South Korea (Nomada aswensis Tsuneki, 1973, Nomada fusca Schwarz, 1986) are reported. The adult external morphology and male genitalia are illustrated with a key to 29 species of Nomada ruficornis species-group in South Korea. Additionally, the flower associations for each species are also provided.